The Routledge handbook of language and creativity - Jones, Rodney H. 1959- (Routledge, 2016)
"The Routledge Handbook of Language and Creativity provides an introduction and survey of the wide range of perspectives on the relationship between language and creativity. Divided into four sections, this handbook covers the dimensions of language and creativity, literary creativity, multimodal and multimedia creativity, and creativity within language teaching and learning. Written by a group of leading academics from around the world, The Routledge Handbook of Language and Creativity will serve as an important reference for students and scholars in the fields of English language studies, applied linguistics, education and communication studies"..
Includes bibliographical references and index
Keywords: LANGUAGE ARTS & DISCIPLINES / General; LANGUAGE ARTS & DISCIPLINES / Linguistics / General; Linguistik; Sprache; Creativity (Linguistics) -- Handbooks, manuals, etc; Language and languages -- Handbooks, manuals, etc; Creation (Literary, artistic, etc.) -- Handbooks, manuals, etc; Kreativität; Aufsatzsammlung